Economics - Hyman, David N. (Chicago : Irwin, 1997)
Providing an overview of all aspects of introductory economics, this text features interviews with distinguished economists. Each chapter includes a "Global Economy" section, helping students understand the increasingly international world.
Includes bibliographical references and index.
oif 16/10/14
Loan
Keywords: Economics